2006
DOI: 10.1016/j.ejcts.2006.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Forty years of glucose–insulin–potassium (GIK) in cardiac surgery: a review of randomized, controlled trials

Abstract: Glucose-insulin-potassium (GIK) solutions have been used in cardiac surgery for more than 40 years. At that time, membrane-polarizing and stabilizing effects on cardiomyocyte's action potential were regarded the main benefit. Two meta-analyses described methodological flaws in the early studies (e.g., case numbers, randomization principles, and levels of significance), and came to clearly different recommendations with regard to the usage of GIK in the therapy of acute myocardial function. During the 70s, as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 58 publications
0
23
1
Order By: Relevance
“…31 The consequences of this potential drawback are still a matter of debate, but none of the meta-analyses of GIK studies has revealed any negative results to date. 32,33 In the current trial, enrolled patients had two or more risk factors for hyperlactataemia and the overall incidence of hyperlactataemia was 60% as we expected, which was higher than the results of previous studies (approximately 20%). [2][3][4][5] Patients developing hyperlactataemia showed higher incidences of renal failure and reoperation and longer durations of ventilator care, ICU and hospital stay regardless of the group in the current trial (data not 560 Roh et al shown).…”
Section: Discussioncontrasting
confidence: 53%
“…31 The consequences of this potential drawback are still a matter of debate, but none of the meta-analyses of GIK studies has revealed any negative results to date. 32,33 In the current trial, enrolled patients had two or more risk factors for hyperlactataemia and the overall incidence of hyperlactataemia was 60% as we expected, which was higher than the results of previous studies (approximately 20%). [2][3][4][5] Patients developing hyperlactataemia showed higher incidences of renal failure and reoperation and longer durations of ventilator care, ICU and hospital stay regardless of the group in the current trial (data not 560 Roh et al shown).…”
Section: Discussioncontrasting
confidence: 53%
“…However, the reader should be aware that a vast body of literature also exists on the use of GIK, insulin-glucose, or insulin alone in critically ill patients (due to various causes) in the intensive care unit, as well as in the cardiac surgery patient. [53][54][55][56][57][58][59][60] Although it is beyond the scope of the present article to review these studies in depth, several highlights of this field are worthy of attention and are presented in the online-only Data Supplement.…”
Section: Gik Insulin-glucose In the Intensive Care Setting And With mentioning
confidence: 99%
“…These drugs may have serious adverse effects including tachycardia, hypotension and increased myocardial oxygen demand. The metabolic resuscitation with insulin has been investigated for many years in cardiogenic shock 14. In both ischaemic and non-ischaemic shock, there is a diversion of myocardial metabolism from fatty acids to preferential carbohydrate oxidation and insulin could stimulate glucose myocardial uptake.…”
Section: Discussionmentioning
confidence: 99%